MOTIVASI PETANI DALAM ALIH FUNGSI LAHAN PISANG MENJADI PADI SAWAH DI KECAMATAN SIPORA SELATAN, KABUPATEN KEPULAUAN MENTAWAI, PROVINSI SUMATERA BARAT - Tience E Pakpahan; Ameilia Zuliyanti Siregar; Romayanti Simamora (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2021)
This research entitled Motivation of Farmers in Changing the Function of Banana Land to Rice Paddy in South Sipora District, Mentawai Islands Regency, West Sumatra Province. The imbalance in meeting the increasing needs of the population and changing consumption patterns in the community requires extensive agricultural land to fulfill food and housing which results in land conversion. The purpose of this research was to determine the level of motivation of farmers and the factors that influence the motivation of farmers in the conversion of banana land to lowland rice. This research uses a descriptive analysis method with a quantitative approach. Methods of data collection using questionnaires and methods of data analysis using a Likert scale and multiple linear regression. The results of the research showed that the motivation level of farmers in changing the function of banana land to lowland rice was very high, namely 83.62%, while the results of multiple linear regression on the factors that influenced the conversion of banana land to lowland rice, obtained the following equation Y= 14.321 + 0.736 X1 + 0.510 X2 - 0.463 X3 + 0.525 X4 - 0.514 X5 + 0.578 X6 - 0.406 X7. A further test using t-count shows that the factors that have a significant effect on the motivation of farmers in the conversion of banana land to lowland rice are age (4.482), education (2.419), income (-3,379), availability of production facilities (3,764), government policy (-3,059), the role of extension workers (2,838) and agricultural production (-2,515).It is predicted that the conversion of banana land to lowland rice is one solution to meet the availability of food security in Kep. Mentawai, West Sumatra.